2020
DOI: 10.3390/microorganisms8050652
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolic Potential of Phenol Degradation in Wastewater Treatment Plant of Crude Oil Refinery: Analysis of Metagenomes and Characterization of Isolates

Abstract: The drilling, processing and transportation of oil are the main sources of pollution in water and soil. The current work analyzes the microbial diversity and aromatic compounds degradation potential in the metagenomes of communities in the wastewater treatment plant (WWTP) of a crude oil refinery. By focusing on the degradation of phenol, we observed the involvement of diverse indigenous microbial communities at different steps of the WWTP. The anaerobic bacterial and archaeal genera were replaced by aerobic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 91 publications
2
17
0
Order By: Relevance
“…The selection of these organisms followed practical considerations and with the intended later application of studying potential microbiome-mediated substance toxification in mind. Both species are biologically relevant (Chiller et al 2001 ; Wang et al 2019 ), have an established potential for xenobiotic metabolism (Egea et al 2017 ; Hanafy et al 2016 ; Sowada et al 2014 ; Viggor et al 2020 ) and have been isolated repeatedly from healthy volunteers at different sites (Khayyira et al 2020 ; Sowada et al 2014 ; Steglinska et al 2019 ; Wang et al 2019 ). Amongst the skin’s Micrococcaceae M. luteus is the predominant species (Chiller et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of these organisms followed practical considerations and with the intended later application of studying potential microbiome-mediated substance toxification in mind. Both species are biologically relevant (Chiller et al 2001 ; Wang et al 2019 ), have an established potential for xenobiotic metabolism (Egea et al 2017 ; Hanafy et al 2016 ; Sowada et al 2014 ; Viggor et al 2020 ) and have been isolated repeatedly from healthy volunteers at different sites (Khayyira et al 2020 ; Sowada et al 2014 ; Steglinska et al 2019 ; Wang et al 2019 ). Amongst the skin’s Micrococcaceae M. luteus is the predominant species (Chiller et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrated that these compounds could be degraded and utilized by the flora. Different studies have reported that microorganisms of the Firmicutes and Proteobacteria can degrade polycyclic aromatic hydrocarbons [ 31 , 32 ], and the microorganisms of the Bacteroidetes can degrade phenols [ 33 35 ]. These microorganisms in the inoculum might be involved in the degradation of organic matter in the extract.…”
Section: Resultsmentioning
confidence: 99%
“…These substrates would be depleted due to microbial activities in the aeration tank, which would then provide the opportunity of certain bacteria that are capable of using remaining phenol and other unused compounds to grow in the microbial recovery tank. In addition, various levels of tolerance to phenol have been reported in different bacteria and mixed cultures (Bera et al 2017;Viggor et al 2020). Such difference in response to varying phenol concentrations will allow for growth of bacteria with diverse capability of phenol catabolism in both tanks.…”
Section: Phylogenetic Analysismentioning
confidence: 99%